Covid-19 Vaccine Acceptance and its Influencing Factors Through a Cross-Sectional Study - I Kadek Wartana; Gustini Gustini; Made Agus Nurjana; Estelle Lilian Mua; Niluh Desy Purnama Sari; Fitriani Fitriani; Alfrida Semuel Ra'bung; Hairil Akbar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Background: The rise in Covid-19 related deaths has led to the implementation of vaccination. Despite this effort, some of the population remains reluctant to get vaccinated, citing various reasons for their hesitation. The objective of this research was to examine the various factors affecting covid-19 vaccination acceptance. Methods: This study adopted a cross-sectional design and was conducted between October and December 2022. This study looked at various independent variables such as sex, education, occupation, family income, health insurance, social assistance, history of Covid-19 infection, and information from the health worker. The main variable of interest was vaccination acceptance. The research involved a group of 133 people. Research data is collected by sending surveys to participants while adhering to Covid-19 health guidelines. The research data was examined using chi square test and logistic regression. This study received ethical approval from the Ethics Committee at Palu Health Polytechnic, Ministry of Health in Indonesia number: 0089/KEPK-KPK/VI/2022. Results: Most of the individuals were involved in favor of accepting the Covid-19 vaccine, with a percentage of 83.5%, whereas only 16.5% declined it. Among the different factors considered, age was found to be the most significant in determining vaccine acceptance compared to having social assistance and information from health workers. Conclusion: Vaccine acceptance varied by age, prioritizing older individuals due to their heightened vulnerability to the Covid-19 virus. It is crucial to further investigate how different factors such as socio-demographic characteristics, vaccine’ knowledge, and trust in the healthcare system interact with each other.